BIAYA TRANSAKSI DALAM PENGELOLAAN KAWASAN KONSERVASI BERBASIS MASYARAKAT - Subhan subhan; Sarini Yusuf (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2014)
The formation of marine sactuay in Saponda Island that require the transaction cost. Transaction cost can be defined as the cost of negotiation, measure and uphold the agreement. This study aimed to estimates the magnitude transaction costs of conservation management that ranging from collecting the information, coordination, decision making and of agreement, until monitoring and supervision. The research indicates that the estimated total cost of the transaction cost to the institutional formation KKL is Rp214.252.500. In addition, KKL management can be said efficient if it is seen from the transaction cost (monitoring enforcement), wich tend to be decrease and stable in the following years.